Effect of Loan to Deposit Ratio, Capital Adequacy Ratio, Return On Equity, and Dividend Payout Ratio on stock prices with Bank Indonesia Interest Rates as Moderating Variables in Banking Companies on the Indonesia Stock Exchange - Hutasoit, Debri Ton Mario; Toni, Nagian; Ariesa, Yeni (International Journal of Social and Management Studies, 2022)
This study aimed to analyze the effect of Loan Deposit Ratio, Capital Adequacy Ratio, Return On Equity, and Dividend Payout Ratio on stock prices with Bank Indonesia interest rates as moderating variables. The research data was collected using secondary data from the financial statements of banking companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sample of issuers was selected by purposive sampling so that 18 companies were selected according to the criteria. The collected data is processed using the Partial Least Square (PLS) data analysis method with the help of SmartPLS software. The results show that there is no influence of Loan to Deposit Ratio, Capital Adequacy Ratio, and Dividend Payout Ratio on stock prices; there is an effect of Return On Equity on stock prices, then Bank Indonesia interest rates cannot moderate the influence of Loan to Deposit Ratio, Capital Adequacy Ratio, Return On Equity, and Dividend Payout Ratio to stock prices.